The pre-pack regulation in the EU Commission proposal for a second insolvency directive - Thery, Adrian (European Insolvency and Restructuring Journal, 2023)
This article draws an analysis of the pre-pack as set forth in the recent EU Commission proposal for a second insolvency directive. We explain the context in which this proposal is born, as well as its main features regarding the pre-pack. Also, this proposal for a directive unveils a certain normative foundation for pre-packs that this article aims to describe. In view of the increasing market interest in pre-packs, this proposal for a Directive is likely to supply a normative context to the professional community.